Evaluating Cytotoxicity of Hyaluronate Targeted Solid Lipid Nanoparticles of Etoposide on SK-OV-3 Cells. (24th April 2014) - Mohammadi Ghalaei, Parviz; Varshosaz, Jaleh; Sadeghi Aliabadi, Hojatollah
Abstract : The epithelial ovarian carcinoma is one of the most fatal gynecological cancers. Etoposide is used in treating platinum-resistant ovarian cancer. Sodium hyaluronate is a substance that binds to the CD44 receptors overexpressed in SK-OV-3 cells of epithelial ovarian carcinoma. The aim of the present work was to study the cytotoxicity effect of hyaluronate targeted solid lipid nanoparticles (SLNs) of etoposide on SK-OV-3 cells. The cytotoxicity of the targeted and nontargeted SLNs of etoposide was compared to free drug on the SK-OV-3 cells by MTT assay method. The cellular uptake of the targeted and nontargeted nanoparticles containing sodium fluorescein was also studied. The difference of cell vitality between nontargeted nanoparticles and also targeted nanoparticles with free drug was significant. Targeted nanoparticles also caused more toxicity than nontargeted nanoparticles (P < 0.05 ). After 4 hours of incubating, the fluorescence was remarkably higher in the cells treated by targeted SLNs rather than nontargeted ones, and there was no observable fluorescence in cells incubated with pure sodium fluorescein. Hyaluronate targeted SLNs containing etoposide increased the cytotoxicity of etoposide on SK-OV-3 cells which may be a worthwhile potential method for reducing the prescribed dose and systemic side effects of this drug in epithelial ovarian carcinoma.